Digital Customer Focus, Innovation, and Sustainable Competitive Advantage in Fresh Food E-Commerce for Enhanced Urban Food Accessibility - Muhdaliha, Eryco; Riyadi, Selamet; Iswati, Heni; Saputro, Adi; David, David (Indo-MathEdu Intellectuals Journal, 2025)
The transformation of e-commerce for fresh food is shaped by the convergence of customer-focused digital strategies, innovation, and the pursuit of sustainable competitive advantage, particularly in enhancing food accessibility in urban areas. This study explores how digital technology and customer-centered innovation contribute to operational efficiency, personalized service delivery, and environmental sustainability across the fresh food distribution network. This research uses a narrative qualitative approach, synthesizing insights from academic literature, industry reports, and case studies to examine the strategic alignment between technology adoption, innovation practices, and competitive positioning. The findings show that digital transformation, including blockchain, precision agriculture, and smart logistics, not only enhances transparency and traceability in the food supply chain but also fosters trust and responsiveness among urban consumers. Fresh food e-commerce platforms leverage this technology to minimize food waste, improve delivery accuracy, and quickly adapt to dynamic demand patterns. Furthermore, this study highlights the role of green innovation in strengthening business sustainability, with digital platforms serving as a key driver for environmental monitoring, consumer engagement, and ethical sourcing.